2007
DOI: 10.1063/1.2729479
|View full text |Cite
|
Sign up to set email alerts
|

Modelling, screening, and solving of optimisation problems: Application to industrial metal forming processes

Abstract: Abstract. Coupling Finite Element (FEM) simulations to mathematical optimisation techniques provides a high potential to improve industrial metal forming processes. In order to optimise these processes, all kind of optimisation problems need to be mathematically modelled and subsequently solved using an appropriate optimisation algorithm. Although the modelling part greatly determines the final outcome of optimisation, the main focus in most publications until now was on the solving part of mathematical optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Li et al [2] reported that the most important problem in sheet metal forming is the compensation of springback. Many efforts have been done to eliminate the springback problem [3,4,5]. Most of them focus on mechanical based methods for increasing sheet tension during sheet bending [6,7,8] which considerably reduces the degree of springback.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [2] reported that the most important problem in sheet metal forming is the compensation of springback. Many efforts have been done to eliminate the springback problem [3,4,5]. Most of them focus on mechanical based methods for increasing sheet tension during sheet bending [6,7,8] which considerably reduces the degree of springback.…”
Section: Introductionmentioning
confidence: 99%